PENERAPAN LITERASI DIGITAL PADA MATA KULIAH PEMBELAJARAN LITERASI DI PERGURUAN TINGGI - Antonius Alam Wicaksono; Rio Febrianto Arifendi (Universitas Tribhuwana Tunggadewi, 2023)
The implementation of digital literacy in literacy education for students in the Elementary School Teacher Education Program at Tribhuwana Tungga Dewi University. The methodology used in this research is quantitative research conducted at the Elementary School Teacher Education Program at Tribhuwana Tungga Dewi University in the even semester of the academic year 2022/2023. The results indicate that the Elementary School Teacher Education Program students have digital literacy skills with a score of 50% for digital access, categorized as sufficient, and a score of 75% for digital literacy competence, categorized as good. Furthermore, the results show that technology usage scored 45% with a sufficient category, while online access scored 70% with a good category. For digital literacy competence, the information and communication aspect scored well, while content creation scored sufficient. In conclusion, this research indicates that technology access plays an important role in enhancing digital literacy among Elementary School Teacher Education Program students at Tribhuwana Tunggadewi University.